How psychopathic traits affect individuals’ trust decisions and outcome evaluations: preliminary ERP evidence - Fengbo Guo; Xiuying Zheng; Leru Zhong; Li Gu; Xiuling Liang (BMC Psychology)
Abstract Individuals with psychopathic traits exhibit a range of maladaptive manifestations, including self-centeredness, interpersonal manipulation, and decline to cooperate. Such individuals may have an antagonistic relationship with trust, which may, in turn, affect their behavioral choices. However, it remains unclear how individuals with psychopathic traits make decisions about trusting strangers. To address this gap, 44 healthy participants were selected from a large pool and divided into low (LP) and high (HP) psychopathic traits group based on their scores on the Levenson self-reported psychopathy scale. The participants who acted as trustors play with strangers in a one-shot trust game, and their responses to the strangers were recorded using electroencephalograms. Results demonstrated the HP showed fewer trust to the strangers, especially following the reciprocity from the trustees. Moreover, The HP exhibited a stronger negative N2 during distrust and a higher dFRN response related to expectation violation after receiving feedback from the trustee. The results shown that individuals with elevated psychopathic traits associated with lower trust in interpersonal interaction, further, they may exert greater effort at cognitive control for the decisions of norm violation, however, they may feel more disappoint when their reciprocal expectation is violated. The study provides preliminary neurophysiological evidence for trust-related decision-making and outcome evaluations in individuals with psychopathic traits.